Kontribusi Guru PAI Dalam Mengembangkan Teknologi Pendidikan Pada Pelajaran Agama Di Masa Pandemi Covid-19 - Unik; Nulhakim, Akbar; Azizah, Siti Nur; Nur Putri, Riska Mutia; Pratiwi, Anggi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
During the pandemic, the use of educational technology to transmit lessons from teachers to students is urgently required. If teachers want students to continue studying using the technology they helped create, it must be adapted to their ability levels. The objective of this study was to determine the participation of Islamic Religious Education instructors in developing online religious education tools and materials across the Covid-19 epidemic. This study is based on a review of the relevant literature. In addition to journals, books, and the internet, there are other sources of data and information. Teachers of the Islamic religion should be actively involved in creating educational technology since they are in the best position to know how Islam should be taught to students and can observe how well their students adjust to new learning environments. Keywords: Educational technology; Islamic Religious Education; Teacher’s contribution.